Efisiensi Pembuatan Faktur Pajak dan Pelaporan SPT Masa PPN Antara DJP Online dan Coretax di CV XYZ - Pramesti, Vella Angelia; Vizandra, Ellyzabeth Putri (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the efficiency of issuing tax invoices and reporting Value Added Tax (VAT) Periodic Tax Returns (SPT Masa PPN) by comparing the DJP Online system and the Coretax Administration System at CV XYZ. The research focuses on comparing the reporting process before and after the use of the Coretax digital system, as well as evaluating its direct impact on the efficiency of VAT reporting for Taxable Entrepreneurs (PKP). A descriptive qualitative method was used, with data collected through observation and documentation. The results show that prior to using Coretax, tax reporting was conducted through two separate applications, e-Faktur and e-SPT, which led to inefficiencies, input errors, and longer processing times. After the implementation of Coretax, the reporting process became more integrated, automated, and time-efficient. The system also supports digital document archiving and offers automatic validation and notifications, thereby reducing the risk of delays and reporting errors. Although technical issues such as internet dependency, system errors, and user adaptation remain, Coretax overall has a positive impact on improving tax administration efficiency and compliance at CV XYZ.